2008
DOI: 10.1001/archderm.144.7.943
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod Treatment of Lentigo Maligna: An Open-Label Study of 34 Primary Lesions in 32 Patients

Abstract: L entigo maligna (LM) is an in situ lesion with a 2% to 50% risk of progression to LM melanoma. 1 Currently, surgery or radiotherapy is usually recommended as the primary treatment for LM. In the literature, the recurrence rates reported for radiotherapy range from 0% to 19%, with a mean recurrence rate of approximately 7%; in addition, radiotherapy carries the risk of causing chronic radiodermatitis or radiation-induced malignant neoplasm. 2 A margincontrolled excision using "slow Mohs" (rush permanent sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…21 Two previous studies 2,4 based on histopathologic assessment of the complete surgical excision specimen reported histopathologic clearance rates of 67% (4 of 6) and 75% (30 of 40) ( Table 2). Their efficacy rates and our rate of 53% (20 of 38) are noted to be lower than those of other studies, 1,3,[5][6][7][8][9][10][11][12][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] which used partial biopsy findings or macroscopic clearance to assess efficacy. Such assessment methods may overestimate treatment efficacy by missing persistent disease.…”
Section: Commentmentioning
confidence: 96%
“…21 Two previous studies 2,4 based on histopathologic assessment of the complete surgical excision specimen reported histopathologic clearance rates of 67% (4 of 6) and 75% (30 of 40) ( Table 2). Their efficacy rates and our rate of 53% (20 of 38) are noted to be lower than those of other studies, 1,3,[5][6][7][8][9][10][11][12][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] which used partial biopsy findings or macroscopic clearance to assess efficacy. Such assessment methods may overestimate treatment efficacy by missing persistent disease.…”
Section: Commentmentioning
confidence: 96%
“…7 In a recent review, the rate of disappearance of the lesion was 91%. 7 However, there is no consensus on the criteria for tumor disappearance.…”
Section: Commentsmentioning
confidence: 98%
“…7 In a recent review, the rate of disappearance of the lesion was 91%. 7 However, there is no consensus on the criteria for tumor disappearance. Some authors use clinical parameters, while others use incisional biopsies after treatment, which is not enough because the full extent of the lesion was not assessed.…”
Section: Commentsmentioning
confidence: 98%
“…In addition, several clinical trials have also been carried out or are undergoing to investigate the anticarcinogenic efficacy of new chemopreventive and anticarcinogenic agents and diverse immunosuppressive therapeutic strategies such as the use of dentritic cells, high-doses of interferon-α (IFN-α) and/or IL-2 and anti-cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) antibody, alone or in combination with current therapies for treating locally advanced, metastatic and recurrent melano-mas [33,66,[107][108][109][110][111][112][113][114][115][116][117][118][119] . The cytotoxic drugs include the specific inhibitors of B-Raf E600V , N-Ras G61K , KIT, EGFR and hedgehog signaling elements.…”
Section: Molecular Targeting Strategiesmentioning
confidence: 99%
“…Among other promising experimental strategies, the results from the clinical trials with a experimental treatment consisting to a topical application of a cream containing 5% an immunomodulatory agent, imiquimod (Aldara) after surgical excision of tumors have revealed that this treatment reduced some melanocytic nevi and melanomain-situ (lentigo maligna) [9,10,[107][108][109]126,127] . Moreover, the data from a Phase Ⅰ/Ⅱ study of a combination of topical imiquimod and intralesional IL-2 have also revealed that its treatment induced a significant clinical response in patients with multiple accessible melanoma metastases by increasing the activated lymphocytes and the production of IFN-γ by peripheral blood mononuclear cells as well as by restoring the Th1/Th2 balance [110,111] .…”
Section: Immunotherapy-based Strategiesmentioning
confidence: 99%